Confirmatory Study of the Multidimensional Scales of Perceived Self-Efficacy with Children - Martins Oliveira, Iris (Pontificia Universidad Javeriana, 2018)
The social cognitive career theory suggests that the development of career self-efficacy expectations begins during the childhood period. The Multidimensional Scales of Perceived Self-Efficacy (MSPSE) has been used to assess adolescents and adults’ career self-efficacy. This study extends this research by assessing the psychometric characteristics of the MSPSE with children. The MSPSE factorial structure, invariance, and concurrent validity were examined with data from 313 fifth- and sixth-grade girls and boys (M age = 10.8). Confirmatory factor analyses suggested a good fit of a hierarchical measurement model. Multi-group analyses suggested configurational and metric invariance across grade levels and across gender for the low-order factors. Still, variability in high-order factor loadings was found across gender. The MSPSE was positively correlated with career exploration and academic achievement. This study supports the use of the MSPSE with children, instills future research on children’s career self-efficacy, and advances practices promoting career preparedness.